ANALISA SISTEM PENGELOLAAN DANA ZISWAF PADA KANTOR CABANG YATIM MANDIRI SIDOARJO - Qhusnul Iva Nur Ayni (ICO EDUSHA, 2021)
Ziswaf (Zakat, Infaq, Shadaqah, Wakaf) is very important for Muslims in worship. Ziswaf is the third pillar of Islam that is obligatory for every Muslim who is able to help his brother who is entitled to receive it. Ziswaf is the obligation of every Muslim who is able to pay it to those who need it more. In essence, Allah gives wealth to every Muslim in his portion. However, the existence of zakat will equalize the wealth of existing human beings. This research is a qualitative descriptive study. The data was obtained from the Head of the Sidoarjo Yatim Mandiri Branch. Secondary data is a reference to Yatim Mandiri Magazine which will complement the existing documentation. Data collection methods that the author uses are interviews and observation. The results of this study indicate that these donor institutions consist of corporations and retail, namely in the form of CSR assistance and individual assistance by way of donations picked up by officers or bank transfers. There are donors for this institution in all areas of Sidoarjo. Most of the donors' payment methods are carried out by pick-up by the officer where the donor will receive proof of payment and the magazine as a medium of da'wah. Keywords: Management, Yatim Mandiri, Ziswaf References Majalah Lembaga Amil Zakat Nasional Yayasan Yatim Mandiri. 2021.Surabaya Pedoman Praktik Kerja Lapangan. Sidoarjo. Sekolah Tinggi Agama Islam An Najjah Indonesia Mandiri. Brosur Lembaga Amil Zakat Nasional Yayasan Yatim Mandiri. 2021. Surabaya Berita diakses dari www.yatimmandiri.org. Pada tanggal 20 Juli 202. FE-UNJ.(2012). Pedoman Praktik Kerja Lapangan. Jakarta:Fakultas Ekonomi Universitas Negeri Jakarta. Pamungkas, Fandi. 2018 PROGRAM STUDI S1 AKUNTANSI FAKULTAS EKONOMI UNIVERSITAS NEGERI JAKARTA. http://repository.fe.unj.ac.id/4237/1/Laporan%20PKL_2018_Fandy%2 0Pamungkas_8335145472_S1%20Akuntansi.pdf.